Combined intrapleural and intrabronchial injection of fibrin glue for closing alveolar pleural fistula: a case report - Alfonso Fiorelli; Italia Odierna; Daniele Scarano; Francesco Caronia; Andrea Failla; Mario Iannotti; Mario Santini; Caterina Pace (Journal of Cardiothoracic Surgery, 2019)
Abstract Background The treatment of persistent air leak is a challenge. Herein, we reported the combined intrabronchial and intrapleural injection of fibrin glue using fiber bronchoscopy to seal off an alveolar pleura fistula developed following necrotizing pneumonia in high-risk patient. Case presentation A 74-year-old man was intubated in emergency for acute ischemic stroke. Percutaneous dilatational tracheostomy was then performed, and 15 days later patient returned to spontaneous breathing. However, he developed alveolar pleural fistula following necrotizing pneumonia with persistent air leaks. The intrabronchial and intrapleural injection of fibrin glue using fiber bronchoscopy sealed off the alveolar pleura fistula after that other endoscopic treatments as bronchial valve and intrabronchial fibrin glue application had failed. Conclusions Our strategy is safe and easy to reproduce. It represents an additional method in the armamentarium of the physicians for the management of PAL when all standard strategies are unfeasible or fail.